Studies in the development of capitalism - "Dobb, Maurice" (London, 1959)
A work of this kind, which is concerned with generalizing about historical development on the basis of material already collected and arranged by other hands, runs a grave danger of falling between two stools, and of displeasing both the economist, who often has little time for history, and the historian, who may dismiss it as insufficiently grounded in the first-hand knowledge that comes from actual field-work. To the economist the author may appear as an irrelevant wanderer from his proper territory, and to the historian as an intruding amateur. Of this danger and of his own imperfect equipment for the task the author has, at least, not been unaware. He has, nevertheless, been encouraged to persevere by the obstinate belief that economic analysis only makes sense and can only bear fruit if it is joined to a study of historical development, and that the economist concerned with present-day problems has certain questions of his own to put to historical data. He has been fortified by the conviction that a study of Capitalism, in its origins and growth, so much neglected by economists (other than those of a Marxist persuasion), is an essential foundation for any realistic system of economics.
Keywords: Capitalism